Study on solidification phenomenon of hot-extracted virgin Coconut Oil (HEVCO) and cold-extracted Coconut Oil (CEVCO) (Cocos nucifera L.) using the Avrami model - Mok, Chi Yan (2018)
Product quality has always been an issue in pastries Some quality attributes such as texture, plasticity and mouthfeel is important because it can determine the marketability of the product. Hence this study aims to study on the solidification phenomena, when stored under decreasing temperatures as well as cooling conditions which best suit final product storage and compare the solidification mechanism of cold-extracted virgin coconut oil (CEVCO) and hot-extracted virgin coconut oil (HEVCO) utilizing gravimetric methods and Avrami model. The final moisture content of grated coconut meat is 0.03% while for sliced coconut meat, it is 0.24%, indicating that water content is more easily removed after sample sizes are reduced. VCO extraction is found to be higher in dried samples;10.96%in sliced coconut and 11.04% in grated coconut, due to lowered moisture content. CEVCO has the lowest fatty acid value,at 0.447% while sliced coconut has the highest fatty acid value, at 0.720%. The weight of solid oil deposited were measured after the 3rd minute onwards and the temperature achieved were recorded. As cold temperatures increase, HEVCO and CEVCO experience increase in Avrami exponent whilst crystal growth rate decreased. When different masses of VCO were used, there is a change of solidification mechanism from n=3 to n=4. This is due to changes in crystal growth formed when mass of VCO was increased. When different mass of VCO is used, HEVCO has higher k values than CEVCO. At isothermal solidification temperatures using DSC, the lowest solidification temperature, at 10°C, releases the highest quantity of heat, indicated by the highest peak. As for non-isothermal solidification, a low cooling rate of 1°C/minute yields the lowest peak maximum, governed by a low supercooling degree, whilst the highest cooling rate yields the highest peak maximum over a narrow temperature range.